THE DEVELOPMENT OF LAB WORK KIT“REACTION RATE CHEMISTRY”TO TRAIN SCIENCE PROCESS SKILL ON REACTION RATE MATTER OF XI GRADE SENIOR HIGH SCHOOL - DWI RACHMAWATI, INTAN (Universitas Negeri Surabaya, 2018)
This research aims to determine the feasibility of lab work KIT Reaction Rate Chemistry that used as an intructional media to train the science process skills on the reaction rate matter of XI grade, the validity seen from the validation requirements, the practicality through student responses to lab work KIT reaction rate chemistry, the effectiveness through student learning outcomes and student activity observation results. This was a research development by Borg & Gall, the research model which is limited to preliminary field testing stage. Praliminary field testing conducted on 12 students of XI grade Science 1 SMAN 2 Mojokerto. The instrument that used in this research is the research paper sheet, validation sheet, student response questionnaire, student activity observation sheet, pretest and posttest sheet. The results showed that the developed of lab work KIT reaction rate chemistry was stated feasible on the validity requirement by obtaining an average percentage of 85.22%. Qualified practicality shown from student’s responses on student interest to lab work KIT aspect obtained an average percentage of 97.92%, on the aspect of easy to understanding the matter obtained an average percentage of 93.75%, and on the aspect of easy to use of lab work KIT as instructional media obtained an average percentage of 95.85%. The feasibility of effectiveness shown from student learning outcomes in which 11 students passed the grade individually so that classical completeness reaches 91.67% with gain included in the